Neonatal intrahepatic cholestasis associated with citrin deficiency (NICCD): a case series of 11 Malaysian patients - Chew, H.B.; Ngu, L.H.; Zabedah, M.Y.; Keng, W.T.; Balasubramaniam, S.; Hanifah, M.J.M.; Kobayashi, K. (Kluwer (now part of Springer), 2010)
Citrin deficiency, aetiologically linked to mutations of SLC25A13 gene, has two clinical phenotypes, namely adult-onset type II citrullinaemia (CTLN2) and neonatal/infantile intrahepatic cholestasis, caused by citrin deficiency (NICCD). Malaysian patients with NICCD, especially of Malay and East Malaysian indigenous descent, have never been reported in the literature. We present the clinical features, biochemical findings and results of molecular analysis in 11 Malaysian children with NICCD. In this case series, all patients manifested prolonged cholestatic jaundice and elevated citrulline levels. The other more variable features included failure to thrive, bleeding diathesis, hypoproteinaemia, abnormal liver enzymes, prolonged coagulation profile, hyperammonaemia, hypergalactosaemia, multiple aminoacidaemia, elevated alpha-feto protein and urinary orotic acid as well as liver biopsies showing hepatitis and steatosis. DNA analysis of SLC25A13 revealed combinations of 851del4 (Ex9), IVS16ins3kb and 1638ins23. Most of our patients recovered completely by the age of 22 months. However, one patient had ongoing symptoms at the time of reporting and one had died of liver failure. Since a small percentage of children with NICCD will develop CTLN2 and the mechanisms leading to this is yet to be defined, ongoing health surveillance into adulthood is essential.